Continuity narratives and evolving policy in the history of chinese trade and investment in Malaysia - Zhu, Bin; Haniff Ahamat (Penerbit Universiti Kebangsaan Malaysia, 2021)
With the development of China’s reform and opening up policy, China’s identity has gradually shifted from a solely foreign investment destination country into one that prioritizes capital exports. Among the capital receiving countries, Malaysia has been definitely attractive. As the first ASEAN country that has fostered diplomatic relations with China, Malaysia instituted friendly exchanges with China more than 2,000 years ago. This paper summarizes the history of investment and trade in the Malaysia and China in the ancient Chinese historical books based on the chronicle, and concludes the characteristics of investment and trade in various periods. With the qualitative method, it specifically analyzes the related research materials and historical writing records and focuses on the reasons why China has been willing to invest in Malaysia. The paper finds both countries’ complementarity of goods, the continuous accumulation of exchanges, mutual understanding, influx of Chinese immigrants, and Malaysia’s unique geographical advantages, which have contributed to the fact that China chose to invest and cooperate in Malaysia for two thousand years. This paper can help understand the development of the China-Malaysia relations and can accelerate understanding between the two countries, thus helping in removing hindrances against Chinese investment in Malaysia due to various modes of incomprehension.